HUBUNGAN ANTARA DAYA LEDAK OTOT LENGAN DAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN SMASH PEMAIN BULUTANGKIS CLUB CUPUMANIK BHAYANGKARA KECAMATAN BANGKO BAGAN SIAPI-API - Bambang Hermanto; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is not optimal yet smash results conducted badminton players Club Cupumanik. This problem is evident from observations of researchers at practice and games, it is suspected because of the explosive power arm muscles and leg muscles a player Club Cupumanik. Therefore, the purpose of this study was to determine the corelation between explosive power arm and leg muscle with the smash ability badminton players Club Cupumanik Bhayangkara. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is explosive power arm muscles, (X2) of explosive power legs muscles while the dependent variable (Y) is the smash badminton. This research data obtained from the tests using two hand medicine ball put, standing broad jump test, and smash badminton test. The sample in this study is the player Club Cupumanik of 20 people (total sampling). Based on the research results can be concluded as follows: From the results obtained explosive power arm muscles had significant corelation to the smash ability badminton players Club Cupumanik Bhayangkara District of Bangko Bagan Siapi-api, characterized by the results obtained by the rhitung 0.48> 0.444 rtabel , From the results obtained explosive power leg muscle had significant corelation to the the smash ability badminton players Club Cupumanik Bhayangkara District of Bangko Bagan Siapi-api, characterized by the results obtained by the rhitung 0.51> rtabel 0.444. Thus, there is a significant corelation together between the explosive power of arm muscles and leg muscles with the Smash ability Badminton players Club players Cupumanik Bhayangkara District of Bangko Bagan Siapi-api, is characterized by the results obtained rhitung 0.73> 0.444 rtabelKeywords : Explosive Power, Arms Muscles, Legs Muscles, Smash, Badminton